Anger control is the most influential risk factor of mobile phone addiction among nursing and midwifery students of Zahedan University of Medical Sciences - Sadegh Dehghanmehr; Fatemeh KordSalarzehi; Najmeh Ghiamikeshtgar; Nahid Mir; Mahsima Banaei Heravan; Farhad Shafeie (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundReligious attitude and anger management are two psychopathological constructs receiving little empirical scrutiny in relation to smart phone addiction, but theoretically should demonstrate significant relationships. Today one of these new media that is used by many people around the world, is the mobile phone. Students are one of the most important groups that are affected by mobile social networks. The aim of this study was to determine religious attitudes and anger management as risk factors of mobile phone addiction in nursing and midwifery students. MethodsThis study was a cross-sectional study involving 200 nursing and midwifery students. Relevant data were collected through demographic information questionnaire, anger management skills questionnaire, religious attitude questionnaire, and mobile phone addiction questionnaire. A multiple regression model was used to examine the relationship between variables. ResultsThe mean age of the research subjects was 22.04 ± 3.30 years. Anger control and religious attitude were a significant risk factors of smartphone addiction (β=-0.500; p=0.000; β= -0.069; p=0.004, respectively). The variables of anger ýcontrol and spiritual attitude can predict and explain 33.6% and 2.7% (36.3% in total) of the ýchanges in the mobile addiction score. Anger control is the most influential risk factor of mobile phone addiction among nursing and midwifery students (Beta = -0.385). ConclusionFindings indicate the importance of controlling anger and strengthening religious attitude in reducing the rate of mobile phone addiction in students. This provides guidance to the future development of smartphone addiction prevention programs for students.